2005
DOI: 10.1016/j.jacc.2005.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Expression of Fas and Recovery of Left Ventricular Function in Patients With Recent-Onset Cardiomyopathy

Abstract: In cardiomyopathy of recent onset, increased expression of Fas and TNFR1 was associated with minimal recovery of LV function. Apoptosis limits myocardial recovery, and represents a potential target for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…Recent clinical studies have indicated that alpha interferon (IFN-␣) (11,21,35,36) and IFN-␤ (29) can reduce the severity of viral myocarditis, inhibiting viral replication and improving cardiac function. Nonetheless, viral myocarditis remains a disease without reliable treatment, and the prognosis remains poor for more than half of patients presenting with clinical symptoms (45).…”
mentioning
confidence: 99%
“…Recent clinical studies have indicated that alpha interferon (IFN-␣) (11,21,35,36) and IFN-␤ (29) can reduce the severity of viral myocarditis, inhibiting viral replication and improving cardiac function. Nonetheless, viral myocarditis remains a disease without reliable treatment, and the prognosis remains poor for more than half of patients presenting with clinical symptoms (45).…”
mentioning
confidence: 99%
“…17 A few serologic and imaging biomarkers have been associated with poor clinical outcome. For example, relatively high serum levels of Fas ligand and interleukin-10 may predict an increased risk of death 18,19 although these assays are not widely available.…”
Section: Diagnosismentioning
confidence: 99%
“…2 is a relevant cause of heart failure leading to increased morbidity and mortality (1,2). The etiology of this disease is currently under intense investigation.…”
Section: Dilated Cardiomyopathy (Dcm)mentioning
confidence: 99%